113k views
1 vote
Solve the equation. Help please!
x^{log_(3)x-4 } = 3^(-3) \\\\x^{log_(2)x } = 16

User Balki
by
5.5k points

1 Answer

4 votes

First equation:


x^(\log_3x-4)=3^(-3)


\log_3\left(x^(\log_3x-4)\right)=\log_33^(-3)


(\log_3x-4)\log_3x=-3\log_33


(\log_3x)^2-4\log_3x=-3


(\log_3x)^2-4\log_3x+3=0


(\log_3x-3)(\log_3x-1)=0


\log_3x-3=0\text{ or }\log_3x-1=0


\log_3x=3\text{ or }\log_3x=1


3^(\log_3x)=3^3\text{ or }3^(\log_3x)=3^1


x=27\text{ or }x=3

Second equation:


x^(\log_2x)=16


x^(\log_2x)=2^4


\log_2\left(x^(\log_2x)\right)=\log_22^4


\log_2x\log_2x=4\log_22


(\log_2x)^2=4


\log_2x=\pm2


2^(\log_2x)=2^(\pm2)


x=2^2\text{ or }x=2^(-2)


\boxed{x=4\text{ or }x=\frac14}

User TLGreg
by
5.8k points